PENYEBARAN HADIS MEDIA SOSIAL: (Studi Atas Perkembangan Kajian Shahih Bukhari Via Youtube dari Tahun 2011-2022) - Rina Rizki Dzakiyyatul Adha Rina Rizki Dzakiyyatul Adha; Hendri Waluyo Lensa Hendri Waluyo Lensa (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
The dissemination and study of Hadith has developed from time to time, including the hadiths contained in the book Sahih Bukhari by Imam Bukhari, including in today's digital era, conventional teaching of hadith has transformed into digital-based teaching via modern communication media in this century. One of the tools used to spread hadith is the social media Youtube. To what extent is the significance and pattern of dissemination and study of the authentic hadiths contained in Sahih Bukhari on Youtube from 2011-2022. The method used as an analytical knife to answer the significance and pattern of distribution and review of the hadiths of the Book of Sahih Bukhari is an analytic descriptive method in which the author collects channels that upload Sahih Bukhari Studies via Youtube from 2011-2022, analyzes titles, calculates average viewers , analyzing the upload date and gathering the speakers for the study of Shahih Bukhari. After the writer conducted a thorough research on the significance of the spread of hadith studies in Sahih Bukhari. The results of this study show that the spread of Shahih Bukhari's studies via Youtube from 2011-2022 has increased quite significantly, this is indicated by the increasing number of channels that upload videos with the theme of Shahih Bukhari's studies each year.